El criterio pedagógico del docente como orientador del papel mediador de las TIC en sus prácticas de aula (2017)
The present research seeks to understand how the pedagogical criterion of the teacher is orienting the mediating role of ICT in three learning environments. In that regard, a qualitative approach is adopted on the basis of a multiple case study, in which three learning environments mediated by ICT are described: a Biology class, a Chemistry class and an English class. Rather than recounting class observations, this study seeks to recreate them from the richness of the perceptions of the different actors, allowing the facts observed to be vividly detailed. Additionally, it presents a cross-sectional analysis of the cases, in which a discussion with the theoretical references that have guided it is set up, from the mediation categories of ICT and reconstruction of the pedagogical criterion of the teacher. In accordance with the data requirements, four instruments were deployed: class observation, in-depth interview, review of written records and focus groups, in which three teachers...